An Aberration-Corrected STEM for Diffraction Studies. - Krivanek, O; Dellby, N; McManama-Smith, A; Murfitt, M; Nellist, P; Own, C (2005)
Extended abstract of a paper presented at Microscopy and Microanalysis 2005 in Honolulu, Hawaii, USA, July 31--August 4, 2005.